Elements to Consider When Establishing the Envisaged Development Bank of Mozambique : Policy Note - Leonardo Vicente, Carlos (World Bank, Washington, DC, 2014)
This note identifies elements to consider when establishing and operating the proposed Development Bank of Mozambique (MDB). It is motivated by the recently circulated draft National Development Strategy which calls for the creation of a development bank to promote economic development by mobilizing and allocating financial resources for long-term investment. The note neither endorses nor opposes the establishment of the proposed development bank in Mozambique. The note is organized as follows: following this introduction, section two highlights recent progress in outreach and access to finance in Mozambique and identifies three market gaps, limited availability of long-term finance, agricultural finance, and Small and Medium Enterprise (SME) finance, which are often cited as reasons for government intervention; section three assesses a potential role for the development bank in addressing these gaps; section four discusses elements to consider when establishing and operating such development bank; and section five concludes.